Features of Modern Marketing in Innovation for Socio-Economic Development - Budovich, Lidia Sergeevna (International Journal of Criminology and Sociology, 2021)
The modern stage of the innovation policy development has been marked by the major breakthrough and the principal changes of the Russian economy resulting in increasing demand for the practical implementation of marketing concepts as a driver of the performance and competitive growth of the domestic production. The special aspects of implementing the modern marketing concepts of innovations is the necessity of simultaneous application of its main tools, i.e. products, prices, distribution, promotion and positioning. At present, if an organization sets an objective to maximize returns, minimize costs and create a positive image of the company, it needs to implement the integrated marketing techniques in practice. The integrated marketing is a high-performance strategy of market interaction that permeates all organization divisions for the successful market penetration, market share gain, strengthening the corporate influence in the target market segment and business financial stability.